Методи та засоби ефективного управління передачею даних в захищених комп’ютерних мережах - Mukhin, V. Ye.; Luay, Darvish (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The analysis of modern means for data transfer control in computer networks, based on TCP/IP protocol is performed. The new method with the packets transfer early delay based on active management of the packets queues in routers and servers is developed. The means for traffic congestion prevention in secured networks are suggested on its basis. The researches of the means for congestion prevention in networks confirmed the efficiency of the suggested methods and means in comparing them to existing, that is especially important for network services realization.